Functional annotation of 19,841 Populus nigra full-length enriched cDNA clones - Seki Motoaki; Futamura Norihiro; Igasaki Tomohiro; Kado Tomoyuki; Nishiguchi Mitsuru; Toyoda Atsushi; Totoki Yasushi; Sakurai Tetsuya; Nanjo Tokihiko; Sakaki Yoshiyuki; Shinozaki Kazuo; Shinohara Kenji (BMC Genomics, 2007)
Abstract Background Populus is one of favorable model plants because of its small genome. Structural genomics of Populus has reached a breakpoint as nucleotides of the entire genome have been determined. Reaching the post genome era, functional genomics of Populus is getting more important for well-comprehended plant science. Development of bioresorce serving functional genomics is making rapid progress. Huge efforts have achieved deposits of expressed sequence tags (ESTs) in various plant species consequently accelerating functional analysis of genes. ESTs from full-length cDNA clones are especially powerful for accurate molecular annotation. We promoted collection and annotation of the ESTs from Populus full-length enriched cDNA clones as part of functional genomics of tree species. Results We have been collecting the full-length enriched cDNA of the female poplar (Populus nigra var. italica) for years. By sequencing P. nigra full-length (PnFL) cDNA libraries, we generated about 116,000 5'-end or 3'-end ESTs corresponding to 19,841 nonredundant PnFL clones. Population of PnFL cDNA clones represents 44% of the predicted genes in the Populus genome. Conclusion Our resource of P. nigra full-length enriched clones is expected to provide valuable tools to gain further insight into genome annotation and functional genomics in Populus.